ANALISIS PERBANDINGAN KINERJA KONTRAKTOR ISO DAN NON ISO PADA PEKERJAAN BETON - Prisma Sistia Putri, Indradi Wijatmiko, Eko Andi Suryo (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2016)
Abstract ISO in the construction sector guarantees the company implements Quality Management System (QMS) consistently. But in reality, not all contractors in Indonesia have certificate and implement QMS ISO. So it is necessary to carry out a comparative of the contractors performance, who are ISO and non ISO certified especially on concrete work as more than 60% of construction projects in Indonesia use concrete. Questionnaires and interview were conducted at the three ISO and three non ISO contractors to determine the differences performance on concrete work. MS Excel 2007, SPSS for Windows Version 22.0, and logistic regression were employed to process the data. SWOT analyses were employed to create the strategies to improve construction company performance associated with the implementation of QMS ISO 9001: 2008. The questionnaires and t test result showed a better perfomance by contractors who have certification of QMS ISO 9001:2008 for the concrete work on the variable of operational, human resources, quality of concrete products, and customers than those who have no ISO certification. Logistic regression showed that the variable of operational in positive significant trend on the contractors performance for concrete work associated with the implementation of QMS ISO 9001: 2008. SWOT analyses result in completion of work according to the procedures, speed in decision making, integrated documentation and communication systems, good relation with sub contractors as the strength. Human resources are less prepared to implement ISO, the performances were not relevant to the quality target, and rework as the weaknesses. Customers and operating environment as the opportunities. Competitors and lack of government support as the threats.Keywords: QMS ISO 9001:2008, performance of ISO and non ISO contractors, logistic regression, SWOT.